Intellectual Property Rights And The Management Of Traditional Knowledge In Indian Agriculture - Gahukar, R.T. (Journal of Knowledge Management Practice, 2010)
India is rich in the diversity of traditional knowledge that has been perpetuated from generation to generation since ancient times. There have been significant changes in farming systems, especially after introduction of the Green revolution, but the intellectual property rights of farmers have been rarely considered by policy makers, researchers and farmers’ cooperatives. At present, tribal communities adopt old techniques that need to be gracefully acknowledged and legally recognized. Proper and timely management of traditional knowledge, combined with improved practices, would certainly be helpful in future agricultural strategies. In this paper, the issues related to intellectual property rights (IPR) and management of traditional knowledge are discussed, and guidelines for further studies and development are outlined.
Keywords: knowledge management; Indian agriculture; Intellectual property rights; traditional knowledge; management practices